A palynological study of the genus Plantago (Plantaginaceae). Issue 6 (1st November 2020) - Mohsenzadeh, Saeed; Sheidai, Masoud; Ghahremaninejad, Farrokh; Koohdar, Fahimeh
Abstract: Pollen morphology of 19 taxa of the genus Plantago was studied and documented in detail using scanning electron microscopy (SEM). The pollen grains are small to medium-sized ( P = 18.7‒44.0 µm, E = 13.7‒34.2 µm), prolate-spheroidal to prolate ( P / E = 1.05‒1.54 µm) in shape and pantoporate. Based on SEM observations of tectum ornamentation, three groups of taxa can be distinguished: the Ovata group with scabrate tectum, the Major group with coarsely verrucate tectum and the Lanceolata group with finely verrucate tectum. Multivariate analyses indicate that, the pollen morphology is not taxonomically significant at the subgenus and section levels, but it is useful for delimitation at the infraspecific level, and also for understanding the morphological diversity at the species level.